Pengaruh Mindset Kewirausahaan, Pemanfaatan Ai, Kreativitas, dan Minat Berwirausaha Terhadap Tingkat Keberhasilan Rintisan Usaha Mahasiswa - Asharryadi Noegroho; Dede Yusuf; Laeli Farkhah; Salwa Dwi Septian B (Jurnal Publikasi Manajemen Informatika, 2024)
This study aims to analyse the influence of entrepreneurial mindset, the use of artificial intelligence (AI), creativity, and entrepreneurial interest on the success rate of student business start-ups. Using a quantitative approach and multiple linear regression methods, this study involved 150 student respondents who had been running a business for at least three months. The results of the analysis showed that the independent variables had a very weak relationship with the success of the start-up, with a coefficient of determination (R²) of 2.3%. Nonetheless, these findings underscore the importance of integrating elements such as entrepreneurial mindset, creativity, and the use of technology in entrepreneurship education to improve students' competitiveness in the market. This study also provides recommendations for higher education institutions to design more structured and technology-based entrepreneurship programmes, in order to support the success of student businesses in a sustainable manner.